Environmental Health Problem in India: Addressing Environmental Health Problems in India: Strategies for a Sustainable Future (Journal of Advances and Scholarly Researches in Allied Education, 2021)
India is a very diverse nation, not only in terms of culture but also in terms of biodiversity. Its favorable geographical position on the globe positions it as the world's sixth most biodiversity nation. Western Ghats and eastern Himalayas, two of the world's two biodiversity hotspots, are situated here. The word world refers to the things that surround us and make life possible. Health is linked to physical fitness in all living organisms, but it is also linked to mental fitness in humans, whether directly or indirectly. As humans, we are directly or indirectly relying on our environments for all of our activities. The climate has a direct effect on our health and immune system. Revaluation of the manufacturing sector Our ecosystem is affected by an unsustainable construction strategy. And have an effect on our health care system, either directly or indirectly. Research related to the appropriate cost-effective intervention strategies and their implementation in Indian context is a big challenge. This paper discusses objective and measures to be taken by the common people and different initiative taken by the government related to environmental Problem impact human health in India and emphasizes to prioritize it according to the need of country.